A posição do aprendiz no discurso dos professores - Gonçalves, Cinthia Ferreira (2013)
Since the 1990 s, Education has been a relevant theme in Brazil, and the Speech-Language Therapist takes part in the discussions to face the issues related to school failure and inclusion of students with special needs. AIM: With the theory that the position of apprentice in the discourse of teachers generates effects in literacy, this study aims to analyze the position that the apprentice occupies in the speech of teachers and it s unfolding. METHOD: this is a qualitative study. Data collection was conducted with a group of teachers from a state-run school, during the Continued Education activity. The discursive data were collected by recording and then transcribed, and were analyzed using the theory of French Discourse Analysis. DATA ANALYSIS: The analysis enabled the identification of: a) the teachers partaking in the dominant ideology of the educational discourse, characterized by an institutionalized, authoritarian speech, where the teacher does not assume a singular position; b) the teachers ideology about what is language, speech and writing acquisition; c) the position of apprentice occupied by the teacher. RESULTS: We were faced with a teacher who was abandoned and devalued, who considers himself incapable as a consequence of his discursive position of not knowing . This is derived from the entrance of several professional in school who occupy the teacher s space in order to educate him; of the establishment of classes for the teacher to attend (ATPC); of the Continued Education Course that identifies the teacher as someone who must remain in education ; of the binomial social failure/school failure that compares any student to a social failure. CONCLUSION: Leading the teacher to doubt what he says and what is said about him is the starting point for a speech-language therapy action with teachers. The possibility of their speeches gaining other meanings would lead the teacher to occupy other positions in the dialogic structure, making room for abandoning the position of apprentice and fighting school failure